Oxygen uptake kinetics during different swimming incremental protocols - de Jesus, K.; Sousa, A.; Ribeiro, J.; Machado, L.; Vilas-Boas, J. P.; Fernandes, R. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The maximal oxygen uptake (VO2max) is one of the areas of interest in swimming performance and training diagnostic. Despite being widely assumed as a standard for maximal aerobic power, less attention has been given to its kinetics, namely during swimming incremental protocols of different step lengths. Since some authors refer to the necessity of using steps of longer duration, it was aimed to compare the VO2 kinetics in three variants of a swimming incremental protocol to assess VO2max. Methods: Four national level swimmers (20.5±3.4yrs, 1.84±0.07m, and 76.5±5.7kg), performed 7x200, 7x300 and 7x400m front crawl incremental protocols until exhaustion, with increments of 0.05m/s and 30s rest intervals between steps, and 24h between each protocol. O2 was measured bxb (averaged every 5s) using a gas analyzer (K4b2) connected to a snorkel. VO2 kinetics was estimated using a double exponential regression model. Amplitudes for exponential terms (A1and A2), time delays (TD1 and TD2) and time constants (ƒÑ1 and ƒÑ2) were assessed, representing the fast (1) and slow (2) components of VO2 kinetics. Significance was set at p.0.05. Results: VO2 kinetics had a similar behavior along the 7x200, 7x300 and 7x400m, respectively: (i) A1 values of 48.7±2.5, 48.5±1.7 and 49.1±1.1ml/kg/min ; (ii) A2 values of 11.2±2.7, 11.9±1.9 and 11.7±1.7ml/kg/min; (iii) TD1 values of 11.3±2.3, 11.6±2.0 and 11.8±2.0s; (iv) TD2 values of 96.5±5.5, 98.7±2.5, 99.2±2.1s; (v) ƒÑ1 values of 48.7±1.5, 50.1±1.6 and 54.3±3.4s; and ƒÑ2 values of 95.7±1.5, 96.5±1.9 and 99.2±1.7s. Discussion: There were no differences in the amplitudes of the VO2 response corresponding to fast (A1) and slow component (A2), corroborating data observed in running and cycling incremental protocols with 6 vs. 4 and 3 min steps duration (Burnley et al., 2001). No differences were observed for TD1, TD2, ƒÑ1 and ƒÑ2. Carter et al. (2000), conducting different incremental running and cycling protocols to assess VO2max, showed that time parameters remains remarkably constant as exercise intensity increased. Moreover, it has been suggested that the constant time parameters obtained in heavy exercise of long duration, might be related to an increase in lactic acidosis (Burnley et al., 2001). These current results suggest that 200 and 300m should be used in detriment of 400 m steps for VO2max assessment in swimming. Furthermore, short steps duration are easy to implement and more specific to the training and competitive swimming requirements.